2009
DOI: 10.1371/journal.pbio.1000017
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Novel PH-Kinase Domain Interface in PKB/Akt Regulation: Structural Mechanism for Allosteric Inhibition

Abstract: Protein kinase B (PKB/Akt) belongs to the AGC superfamily of related serine/threonine protein kinases. It is a key regulator downstream of various growth factors and hormones and is involved in malignant transformation and chemo-resistance. Full-length PKB protein has not been crystallised, thus studying the molecular mechanisms that are involved in its regulation in relation to its structure have not been simple. Recently, the dynamics between the inactive and active conformer at the molecular level have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
228
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(234 citation statements)
references
References 25 publications
6
228
0
Order By: Relevance
“…Previous studies have shown that AKT allosteric inhibitors require an intact PH-KD interface, because such inhibitors preferentially bind the closed PH-in conformation (16,17,38). Consistent with this result, we found that mutations in AKT that favor an open (PH-out) conformation show reduced sensitivity to allosteric AKT inhibitors, although they retain sensitivity to ATP-competitive inhibitors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that AKT allosteric inhibitors require an intact PH-KD interface, because such inhibitors preferentially bind the closed PH-in conformation (16,17,38). Consistent with this result, we found that mutations in AKT that favor an open (PH-out) conformation show reduced sensitivity to allosteric AKT inhibitors, although they retain sensitivity to ATP-competitive inhibitors.…”
Section: Discussionsupporting
confidence: 90%
“…Recent molecular modeling and structure-based studies suggest that, under basal conditions, interactions between the PH and KD maintain AKT in a closed conformation (PH-in) (15)(16)(17). In this state, PDK1 is unable to access and phosphorylate T308.…”
mentioning
confidence: 99%
“…Specifically, we tested whether rapamycininduced phosphorylation of the hydrophobic motif site in Sin1 Ϫ/Ϫ MEFs was prevented by 1) an inhibitor of PI3K (wortmannin) or 2) an allosteric inhibitor of Akt (Akti VIII) that locks Akt in an inactive conformation and prevents the PH domain from disengaging and binding to membranes (17). As reported above, treatment with rapamycin rescued Ser-473 phosphorylation of Akt (Fig.…”
Section: Rescue Of Ser-473 Phosphorylation In Sin1 ϫ/ϫ Mefs Is Dependmentioning
confidence: 87%
“…Once processed by phosphorylation at the turn motif site, Akt localizes to the cytosol, where it is maintained in an inactive conformation through the interaction between its PH and kinase domains (17). In the presence of proliferative signals, PI3K is activated and generates the lipid second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ).…”
mentioning
confidence: 99%
“…We used Akt Inhibitor VIII, a selective, reversible Akt inhibitor that blocks PH (pleckstrin homology) and kinase domains interactions. This restricts phosphorylation of Akt at Thr308 and Ser473, reduces the levels of active Akt in cells, and blocks the phosphorylation of known Akt substrates (26). SUIT-2 cells were treated with Akt Inhibitor VIII at 5 M or 20 M or with dimethyl sulfoxide (DMSO) prior to infection with wild-type VV, and a standard internalization assay was performed as detailed in Materials and Methods (Fig.…”
Section: Resultsmentioning
confidence: 99%